Deciphering carbon sources of mussel shell carbonate under experimental ocean acidification and warming. (November 2018) - Lu, Yanan; Wang, Li; Wang, Lianshun; Cong, Yuting; Yang, Guojun; Zhao, Liqiang
Abstract: Ocean acidification and warming is widely reported to affect the ability of marine bivalves to calcify, but little is known about the underlying mechanisms. In particular, the response of their calcifying fluid carbonate chemistry to changing seawater carbonate chemistry remains poorly understood. The present study deciphers sources of the dissolved inorganic carbon (DIC) in the calcifying fluid of the blue mussel ( Mytilus edulis ) reared at two pH (8.1 and 7.7) and temperature (16 and 22 °C) levels for five weeks. Stable carbon isotopic ratios of seawater DIC, mussel soft tissues and shells were measured to determine the relative contribution of seawater DIC and metabolically generated carbon to the internal calcifying DIC pool. At pH 8.1, the percentage of seawater DIC synthesized into shell carbonate decreases slightly from 83.8% to 80.3% as temperature increases from 16 to 22 °C. Under acidified conditions, estimates of percent seawater DIC incorporation decreases clearly to 65.6% at 16 °C and to 62.3% at 22 °C, respectively. These findings indicate that ongoing ocean acidification and warming may interfere with the calcification physiology of M. edulis through interfering with its ability to efficiently extract seawater DIC to the calcifying front. Highlights: Sources of Mytilus edulis shell carbonate are deciphered through carbon isotopic analysis. With increasing temperature, the percent metabolic carbon incorporation into shell increases. Exposure to low pH also results in an increase of metabolic carbon taken up into shell. Ongoing climate change reduces the ability of M. edulis to extract seawater carbon to calcify.